ONLINE BLOGS AS AN EDUCATIONAL TOOL IN FINLAND FOR INVESTMENT PRODUCT FUNCTIONALITIES - Jauhiainen, Juuso (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The purpose of this research is to examine what exchange traded investment products are, how they function and how these functionalities are brought to light in blogs written by financially incentivized authors. Oftentimes the blogs are educational in nature and this research studies if they cover enough information for a beginner investor to understand the risks and attributes of these products. A comprehensive sample of blogs covering exchange traded investment products in Finnish is chosen that cover the chosen product groups. The texts of these blogs is compared against a set of the most important attributes of these products. The analysis is based on whether some attributes are emphasized while some left for less attention or completely out of the blog. The research shows that the educational blogs written on these products are not thorough enough on explaining the risks and costs of these products for a beginner investor to understand them. The blogs often do not disclose that the explanation on the product is not thorough and the investor should learn more about them before investing. The blogs on these products could be called marketing material that is in no way regulated.